Pulsed radiofrequency to the dorsal root ganglion or the sciatic nerve reduces neuropathic pain behavior, decreases peripheral pro-inflammatory cytokines and spinal β-catenin in chronic constriction injury rats. Issue 7 (14th May 2019) - Jiang, Ren; Li, Ping; Yao, Yong-Xing; Li, Hong; Liu, Rongjun; Huang, Ling-Er; Ling, Sunbin; Peng, Zhiyou; Yang, Juan; Zha, Leiqiong; Xia, Li-Ping; Chen, Xiaowei; et al.
Abstract : Background and objectives: Pulsed radiofrequency (PRF) is a minimal neurodestructive interventional pain therapy. However, its analgesic mechanism remains largely unclear. We aimed to investigate the peripheral and spinal mechanisms of PRF applied either adjacent to the ipsilateral L5 dorsal root ganglion (PRF-DRG) or PRF to the sciatic nerve (PRF-SN) in the neuropathic pain behavior induced by chronic constriction injury (CCI) in rats. Methods: On day 0, CCI or sham surgeries were performed. Rats then received either PRF-DRG, PRF-SN, or sham PRF treatment on day 4. Pain behavioral tests were conducted before surgeries and on days 1, 3, 5, 7, 9, 11, 13, and 14. After the behavioral tests, the rats were sacrificed. The venous blood or sciatic nerve samples were collected for ELISAs and the dorsal horns of the L4–L6 spinal cord were collected for western blot examination. Results: The mechanical allodynia and the thermal hyperalgesia has been relieved by a single PRF-DRG or PRF-SN application. In addition, the analgesic effect of PRF-DRG was superior to PRF-SN on CCI-induced neuropathic pain. Either PRF-DRG or PRF-SN reversed the enhancement of interleukin 1β (IL-1β) and tumor necrosis factor alpha (TNF-α) levels in the blood of CCI rats. PRF-DRG or PRF-SN also downregulated spinal β-catenin expression. Conclusions: PRF treatment either to DRG or to sciatic nerve reduced neuropathic pain behavior, and reduced peripheral levels of pro-inflammatory cytokines and spinal β-catenin expression in CCI rats. PRF to DRG has a better analgesic effect than PRF to the nerve.